Meningkatkan Kinerja Guru SD Swasta dengan Kepemimpinan Transformasional, Motivasi dan Komitmen Organisasi (Studi Kasus pada Sekolah Dasar Swasta di Kota Depok) - Trirahayu, Dewi; Kurniawati, Dewi (SEKOLAH PASCASARJANA PRESS, 2019)
This study purpose to determine the significant effect of transformational leadership, motivation and organizational commitment to teacher performance. The study was conducted by processing primary data as a result of filling out questionnaires by 90 Private Primary School Teachers as samples spread in Depok City. This study uses Multiple Linear Regression analysis, correlation analysis and coefficient of determination. The results of the study concluded that transformational leadership, motivation and organizational commitment significantly influence to teacher performance. Transformational leadership has a significant effect to teacher performance. Motivation has a significant effect to teacher performance. Organizational commitment has a significant effect to teacher performance. This means that the better transformational leadership, motivation and organizational commitment can improve teacher performance.